Postimplantation Whole Embryo Culture Assay for Hamsters: An Alternative to Rat and Mouse - Bogdan Wlodarczyk; Bogumil Biernacki; Maria Minta; Jan Zmudzki (The Scientific World Journal)
Postimplantation whole embryo culture (WEC) assay for rats and mice has been well established and introduced to many laboratories. Recently WEC technique for rabbits has been developed; however, information on culture of other species is very limited. Knowing the usefulness of hamsters in classical embryotoxicology, we reasoned that hamster WEC could be an alternative model for the most frequently used rat and mouse WEC. Previously we have optimized culture conditions for postimplantation hamster embryos. The aim of this study was to test the susceptibility of hamster embryos cultured in vitro to embryotoxic compounds and to compare our results with those reported by others on rat or mouse embryo culture. For that purpose we choose three known embryotoxic compoundsvalproic acid, cadmium chloride, and diethylstilbestroland tested them using a postimplantation hamster whole embryo culture assay. Hamster embryos were cultured from 7.5 days gestation for 24 h in a medium consisting of 35% hamster serum and 65% synthetic culture medium (Iscoves or McCoy 5A). At the end of the culture period, the embryos were examined morphologically, measured with the aid of a computer image analysis system, and total protein content was assessed. All three compounds exhibited dose-related embryotoxic and teratogenic effects in hamster embryos. The malformations observed were similar to those reported on rat and mouse embryos. Comparison of the results with data reported by other authors indicates that hamster embryos cultured in vitromight be more susceptible to embryotoxic stimuli than rat and mouse embryos.